Can Minimally Invasive Esophagectomy Replace Open Esophagectomy for Esophageal Cancer? Latest Analysis of 24, 233 Esophagectomies From the Japanese National Clinical Database. Issue 1 (July 2020) - Yoshida, Naoya; Yamamoto, Hiroyuki; Baba, Hideo; Miyata, Hiroaki; Watanabe, Masayuki; Toh, Yasushi; Matsubara, Hisahiro; Kakeji, Yoshihiro; Seto, Yasuyuki
Abstract : Objective: We aimed to elucidate whether minimally invasive esophagectomy (MIE) can be safely performed by reviewing the Japanese National Clinical Database. Summary of Background Data: MIE is being increasingly adopted, even for advanced esophageal cancer that requires various preoperative treatments. However, the superiority of MIE's short-term outcomes compared with those of open esophagectomy (OE) has not been definitively established in general clinical practice. Methods: This study included 24, 233 esophagectomies for esophageal cancer conducted between 2012 and 2016. Esophagectomy for clinical T4 and M1 stages, urgent esophagectomy, 2-stage esophagectomy, and R2 resection were excluded. The effects of preoperative treatment and surgery on short-term outcomes were analyzed using generalized estimating equations logistic regression analysis. Results: MIE was superior or equivalent to OE in terms of the incidence of most postoperative morbidities and surgery-related mortality, regardless of the type of preoperative treatment. Notably, MIE performed with no preoperative treatment was associated with significantly less incidence of any pulmonary morbidities, prolonged ventilation ≥48 hours, unplanned intubation, surgical site infection, and sepsis. However, reoperation within 30 days in patients with no preoperative treatment was frequently observed after MIE. The total surgery-related mortality rates of MIE and OE were 1.7% and 2.4%, respectively ( P < 0.001). Increasing age, low preoperative activities of daily living, American Society of Anesthesiologists physical status ≥3, diabetes mellitus requiring insulin use, chronic obstructive pulmonary disease, congestive heart failure, creatinine ≥1.2 mg/dL, and lower hospital case volume were identified as independent risk factors for surgery-related mortality. Conclusions: The results suggest that MIE can replace OE in various situations from the perspective of short-term outcome. Abstract : Supplemental Digital Content is available in the text